Spatial Analysis of Fiscal Balance Fund on Income Inequality in West Kalimantan - Amelia Amelia; Tri Diana (Jurnal Economia, 2021)
Abstract: The research aims to analyze the effect of fiscal balance fund on income inequality in West Kalimantan by considering spatial inter-relationships between existing districts/cities. The study showed that the Spatial Durbin Model with fixed effect was empirically suitable. A variant of spatial autoregression model using Gini Ratio during the period of 2010 – 2018 in 14 districts/cities of West Kalimantan. The study concludes that income disparities between districts/cities were low and constant or the income was relatively distributed per capita. Spatial interactions between districts/cities and their neighbors are also relatively low. Spatial aspect, fiscal balance fund and regional minimum wage have a significant negative effect. On the contrary, the industrial workforce, educated workforce and medical personnel do not affect income inequality in West Kalimantan. This study provides academics with the understanding of the importance of spatial dependence in income inequality model because the economic activity is always related to the neighbor.Keywords: fiscal balance fund, income inequality, spatial aspect Analisis Spasial Dana Perimbangan Terhadap Disparitas Pendapatan Kalimantan BaratAbstrak: Penelitian ini bertujuan menganalisis pengaruh dana perimbangan terhadap disparitas pendapatan di Kalimantan Barat dengan mempertimbangkan keterkaitan spasial antar kabupaten/kota yang ada. Studi ini menghasilkan pemilihan model spasial durbin dengan efek tetap secara empiris sudah tepat. Variansi dari model autoregresif spasial menggunakan Indeks Gini kurun waktu 2010–2018 silang tempat dari 14 kabupaten/kota di Kalimantan Barat. Hasil penelitian menyimpulkan disparitas pendapatan antar kabupaten/kota rendah dan konstan atau relatif merata dalam pendapatan per kapita. Interaksi spasial antar kabupaten/kota dengan tetangganya juga relatif rendah. Aspek spasial, dana perimbangan dan UMR secara negatif signifikan mempengaruhi disparitas pendapatan. Sedangkan tenaga kerja industri, tenaga kerja terdidik dan tenaga medis tidak mempengaruhi disparitas pendapatan di Kalimantan Barat. Penelitian ini memberikan wawasan bagi kalangan akademisi tentang pentingnya memasukkan spatial dependence kedalam model ketimpangan pendapatan karena proses kegiatan ekonomi selalu berkaitan dengan wilayah tetangga.Kata kunci: dana perimbangan, disparitas pendapatan, aspek spatial